2017
DOI: 10.1159/000477735
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Adenocarcinoma of the Retinal Pigment Epithelium: An Immunohistochemical and Electron Microscopic Study

Abstract: Purpose: Retinal pigment epithelium (RPE) adenocarcinoma is a very rare malignant intraocular tumor. Herein we describe the histopathological features of RPE adenocarcinoma. Case: A 36-year-old male was referred to our clinic because of floaters in his left eye. The initial diagnosis was malignant melanoma of the choroid. We resected the tumor and studied it histopathologically. The tumor tissue was investigated by light microscopy including immunohistochemistry using antibodies against S-100, HMB-45, EMA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A particularly important feature of RPE adenocarcinoma is the occasional presence of a dilated retinal feeder vessel [12]. Shields et al [3] found dilated retinal vessels in 8 of 13 RPE tumours in their study, which were accentuated on fluorescein angiography.…”
Section: Literature Reviewmentioning
confidence: 97%
See 4 more Smart Citations
“…A particularly important feature of RPE adenocarcinoma is the occasional presence of a dilated retinal feeder vessel [12]. Shields et al [3] found dilated retinal vessels in 8 of 13 RPE tumours in their study, which were accentuated on fluorescein angiography.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In the middle of the spectrum, there are lesions for which no clear distinction between hyperplasia and true neoplasms can be made, either clinically or histologically [11]. It has been acknowledged that RPE tumours can arise from reactive hyperplasia and metaplasia following trauma, inflammation, or degenerative processes that involve the choroid or retina [12]. They have been reported to arise from congenital hypertrophy of the retinal pigment epithelium (CHRPE) as well [13][14][15][16][17][18].…”
Section: Pathogenesis and Nomenclaturementioning
confidence: 99%
See 3 more Smart Citations